Exploring the Signification of visible face makeup among Nigerian Women - Obiageri Solomon-Etefia, Patience; Odo Onu, John (International Journal of Arts, Languages, Linguistics and Literary Studies, 2022)
This paper examines visible face make-up women wear in Nigeria. The study aims to highlight the signs of women make-up. This study employs a qualitative research methodology, which include oral interview and observation methods for data collection. Ten women and two make-up artist were used as informant in this paper. The data were analysed using semiotics theory. The study also shows that women wear make-up not only to be beautiful, but to join the moving train and for facial correction. There are specific laws and rules in make-up application that define the appearance code with the use of the make-up functional materials. Foundation goes on the face, mascara on the eyes and lipstick on the lips. All of these make-up functional have their various signs and symbols. Foundation symbolizes glue as it binds the different ingredients; concealer signifies weapon and so on. The observed makeovers that women wear in Nigeria are; gothic, nude, engagement/bridal, editorial, party and permanent. Each of them have their significance, for instance, the gothic make up signifies loudness, and nude signifies softness, and so on. The colours are also very significant in makeovers. The blue colour is a symbol of masculinity, red colour a symbol of power and yellow a symbol of hope.